2013
DOI: 10.6028/nist.tn.1812
|View full text |Cite
|
Sign up to set email alerts
|

Best Practices Guide for High-Volume Fly Ash Concretes : Assuring Properties and Performance

Abstract: A best practices guide is developed from a synthesis of recent research on high-volume fly ash (HVFA) concrete mixtures. These best practices can be applied by the concrete construction industry to achieve desired properties and to ensure the (high) performance of HVFA concrete mixtures in practice. As such, the report considers all aspects of HVFA concrete production, from the characterization of the starting materials, through mixture proportioning and curing options to achieve desired properties, to the in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 41 publications
0
15
0
3
Order By: Relevance
“…A Uncertainties in density represent one standard deviation for ten replicate measurements. 1 Certain commercial products are identified in this paper to specify the materials used and the procedures employed. In no case does such identification imply endorsement or recommendation by the National Institute of Standards and Technology, nor does it indicate that the products are necessarily the best available for the purpose.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Uncertainties in density represent one standard deviation for ten replicate measurements. 1 Certain commercial products are identified in this paper to specify the materials used and the procedures employed. In no case does such identification imply endorsement or recommendation by the National Institute of Standards and Technology, nor does it indicate that the products are necessarily the best available for the purpose.…”
Section: Methodsmentioning
confidence: 99%
“…While high-volume fly ash (HVFA) concrete mixtures have been promoted and occasionally employed for many years, they have received renewed attention during the recent concrete sustainability movement [1]. Recent investigations have indicated that one of the drawbacks of such mixtures, excessive setting time delays, can be alleviated by the judicious volume-based replacement of 1 = 4 of the fly ash in a mixture by a fine limestone powder with a median particle diameter on the order of 1 lm [2].…”
Section: Introductionmentioning
confidence: 99%
“…To a first approximation, the grout hydration enthalpy (heat generation) is assumed to be proportional to the Portland cement complement with negligible enthalpic contribution by the fly ash. This assumption is slightly non-conservative because, as noted, fly ash contributes perhaps 15% as much heat as an equal mass of Portland cement (ACI 2002; Table 4 of Langan et al 2002; Figure 3.13 of Kim 2010; Figure 3 of Bentz et al 2013) and the amount of heat decreases with the complement of calcium oxide in the fly ash, which is generally lower for Class F fly ash (Thomas 2007). Furthermore, the heat contribution by fly ash occurs much later than that of Portland cement so it does not add to the thermal power generation maximum for Portland cement that occurs at room temperature about 8 to 12 hours after mixing with water.…”
Section: 3mentioning
confidence: 99%
“…of Langan et al 2002; Figure 3.13 of Kim 2010;Figure 3ofBentz et al 2013). The benefit of fly ash substitution in decreasing hydration heat increases by decreasing the complement of calcium oxide, CaO, in the fly ash(Thomas 2007).…”
mentioning
confidence: 99%
“…Of all the ingredients in concrete (the primary ones being cement, supplementary cementitious materials, water, and coarse and fine aggregates), cement has the largest footprints when it comes to both carbon dioxide release and energy consumption. While the feasibility of achieving higher levels (greater than 50 %) of cement replacement using fly ash, a residual product from coal combustion, has been demonstrated in the laboratory and in practice [2, 3], questions remain about the stability of the supply of quality fly ash and local shortages have indeed been encountered in parts of the U.S. in recent years. Similarly, high replacement mixtures using slag have demonstrated good performance [4, 5], but the worldwide slag supply is quite limited when compared to the annual demand for concrete for new construction and repair.…”
Section: Introductionmentioning
confidence: 99%